2012
DOI: 10.1111/j.1541-4337.2011.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Iodized Salt in Processed Foods in Select Countries Around the World and the Role of Food Processors

Abstract: Executive Summary: The Micronutrient Initiative (MI) issued the Institute of Food Technologists (IFT) a project to assess the extent to which iodized salt is used in processed foods, as well as food processors' level of knowledge on iodine nutrition. Iodine is an essential micronutrient required by the body that is found in a limited number of foods, thus many individuals require additional sources of iodine to meet their daily requirement. Without these additional sources, a range of disorders referred to as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 61 publications
(72 reference statements)
0
20
0
Order By: Relevance
“…Therefore the share of iodized salt in the total amount of salt contained in processed foods could be further improved. Trends in industrialized countries show that individuals are consuming most of their salt through processed foods ( 58 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the share of iodized salt in the total amount of salt contained in processed foods could be further improved. Trends in industrialized countries show that individuals are consuming most of their salt through processed foods ( 58 ) .…”
Section: Discussionmentioning
confidence: 99%
“…While voluntary use of iodized salt in processed foods is permitted in New Zealand, manufacturer uptake is minimal (7) . Following a recent worldwide survey of food manufacturers, it was concluded that iodized salt use in processed foods may need to be mandated to secure manufacturer uptake (28) . The initial report produced by Food Standards Australia *Median iodine intake from foods (excluding iodine-fortified bread and iodized salt) 5 60 mg/d (14) ; estimated iodine intake from iodized salt, if used 5 48 mg/d (1 g salt/d iodized at 48 mg/kg salt) (7,15) ; estimated iodine intake from iodine-fortified bread 5 14 mg/slice (43 mg iodine/100 g bread, 1 slice 5 33 g) (12,13) .…”
Section: Discussionmentioning
confidence: 99%
“…Iodine deficiency disorders (IDD) is a significant public health problem in more than 50 countries. According to WHO, an estimated 2 billion people worldwide (35.2% of the world population) suffer from insufficient iodine intake, defined as urinary iodine levels below 100 μg/L [2]. As a result, twenty-two million children globally each year are at risk of impaired intellectual function and lower school performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Iodine is found naturally in topsoil and top soil has been lost due to deforestation, erosion and flooding thus food crops lack iodine resulting in dietary iodine deficiency. School children, pregnant and lactating mothers are vulnerable to the problem [2].…”
Section: Introductionmentioning
confidence: 99%